"This work that we're doing is bigger than ourselves": A qualitative study with community‐based birth doulas in the United States. Issue 3 (7th July 2022) - Kett, Paula M.; van Eijk, Marieke S.; Guenther, Grace A.; Skillman, Susan M.
Abstract: Context: Community‐based birth doulas support pregnant women, transgender men, and gender non‐binary individuals during the perinatal period and provide essential services and expertise that address health inequities, often taking on additional roles to fill systemic gaps in perinatal care in the United States (US). Despite the benefits that community‐based birth doulas provide, there is little research exploring the work‐ related conditions and stressors community‐based doulas experience. To address this gap, we examined the work experiences, related stressors, and stress management strategies of individual community‐based birth doulas. Methods: In this qualitative, descriptive study we conducted 18 interviews in March through June 2021 with individuals who self‐identified as community‐based doulas working in underserved communities in the US. We analyzed the interviews for themes, which we defined and finalized through team consensus. Results: The doulas reported engaging in specific strategies in their work to address perinatal inequities. They also described facing several work‐related stressors, including witnessing discrimination against clients, experiencing discrimination in medical environments, and struggling with financial instability. To mitigate these stressors and job‐related challenges, interviewees reported they relied on doula peer support and reconnected with their motivations for the work. Conclusions: Community‐based doulas provide essential services and expertise which address inequities and systemic gaps in perinatal care. However, as they work to improve perinatal health, doulas themselves are providing equity work amidst an inequitable system and with insufficient political or financial support. Increased compensation and systemic support which acknowledges the breadth of services provided is needed to strengthen and sustain this critical part of the perinatal workforce.